# Evaluate the idefinite integral integrate of (x^4+1)(sin(x))dx

### 1 Answer | Add Yours

You need to use the property of linearity of integrals such that:

`int (x^4+1)sin x dx = int x^4 sin x dx + int sin x dx`

You should evaluate the integral `int x^4 sin x dx` using integration by parts such that:

`int udv = uv - int vdu`

`u = x^4 => du = 4x^3 dx`

`dv = sin x dx => v = -cos x `

`int x^4 sin x dx = -x^4 cos x +4 int x^3 cos x dx`

You need to use parts to solve `int x^3 cos x dx` such that:

`u = x^3 => du = 3x^2 dx`

`dv = cos xdx => v = sin x`

`int x^3 cos x dx = x^3 sin x - 3int x^2 sin x dx`

`int x^4 sin x dx = -x^4 cos x +4(x^3 sin x - 3int x^2 sin x dx)`

You need to solve `int x^2 sin x dx` using parts such that:

`u = x^2 => du = 2xdx`

`dv = sin x dx => v = - cos x`

`int x^2 sin x dx = -x^2 cos x + 2 int x cos x dx`

`int x^4 sin x dx = -x^4 cos x +4(x^3 sin x - 3(-x^2 cos x + 2 int x cos x dx))`

You need to integrate `int x cos x dx` using parts such that:

`u = x => du = dx`

`dv = cos x dx => v = sin x`

`int x cos x dx = x sin x - int sin x dx`

`int x cos x dx = x sin x + cos x + c`

`int x^4 sin x dx = -x^4 cos x +4(x^3 sin x - 3(-x^2 cos x + 2(x sin x + cos x))) + c`

`int x^4 sin x dx = -x^4 cos x +4(x^3 sin x - 3(-x^2 cos x + 2xsin x + 2 cos x)) + c`

`int x^4 sin x dx = -x^4 cos x + 4(x^3 sin x + 3x^2 cos x - 6x sin x - 6 cos x) + c`

`int x^4 sin x dx = -x^4 cos x + 4x^3 sin x + 12 x^2 cos x - 24 x sin x - 24 cos x + c`

`int (x^4+1)sin x dx = -x^4 cos x + 4x^3 sin x + 12 x^2 cos x - 24 x sin x - 24 cos x - cos x + c`

`int (x^4+1)sin x dx = -x^4 cos x + 4x^3 sin x + 12 x^2 cos x - 24 x sin x - 25 cos x + c`

**Hence, evaluating the given integral, under the given conditions, yields** `int (x^4+1)sin x dx = -x^4 cos x + 4x^3 sin x + 12 x^2 cos x - 24 x sin x - 25 cos x + c.`